Semiochemical studies of Gonipterus sp. 2 (Curculionidae) and pheromone-based masstrapping of Nudaurelia clarki (Saturniidae) in South Africa - Bouwer, Marc Clement (University of Pretoria, 2022)
Dissertation (MSc (Chemistry))--University of Pretoria, 2020.